Right Node Raising and Nongrammaticality. (8th August 2016) - Larson, Brooke
Abstract: Right node raising sentences (RNR) have proved to be difficult for modern syntactic theory to account in an explanatory fashion. In this paper I argue that the reason for this difficulty is that RNR cannot be fully analyzed as a construction independent of online parsing. I argue against current and possible grammatical analyses of the construction and posit that the interpretation of the shared material in the first conjunct is effectively illusory. That is, the interpretive relation between the shared material in RNR and the gap position in the first conjunct is not encoded in the offline representation of the construction, but rather is only captured via a transitory online parsing operation. This analysis has consequences for the relation between the grammar and the parser as well the limits of grammatical relations.